Nonlinear fiber optical parametric amplifiers and lasers with idler removal filter - Yeo, Kwok Shien (2013)
Nonlinear phenomena in optical fiber have been seen detrimental to the performance of fiber optical communication systems; however, in many niche areas optical fiber nonlinear properties are very much desired. Nonlinear Four-wave mixing (FWM) process in optical fiber is generally referred as fiber optical parametric process, for the reason that fiber parameters are deliberately designed to enhance the efficiency of FWM. Among the most important parameters that define the parametric process are the chromatic dispersion profile (related to second-order dispersion), dispersion slope (related to forth-order dispersion), zero-dispersion wavelength and fiber nonlinear coefficient. Silica-based highly nonlinear fibers (HNLFs) are the fiber medium of choice in most parametric experiments mainly because of its excellent fiber attenuation performance and low splice-loss when connected to standard single mode fiber (SMF). Even though HNLF and SMF are both silica-host optical fibers, they are nevertheless incompatible in several fiber characteristics, in which most prominently is their fiber dispersion profile. Incorporating HNLF to an SMF-based system would lead to a phenomenon known as wavelength-dependent gain modulation, where parametric gain ripples exist across the spectrum, with peak and notch gain difference as much as 20 dB. The origin of the gain ripples is investigated theoretically and experimentally. Investigation indicates that by suppressing the idler power by 60 dB, the gain ripples can be smoothened and thus restore the original gain shape of the parametric devices, but with tolerable gain loss around 6 dB. The idler removal filters (IRFs) then become the key enabling device for fiber optical parametric devices with two-segment design as well as double-pass pump configuration. Properly designed IRFs are proven to successfully smoothen gain ripples that exist in a two-segment fiber optical parametric amplifier (FOPA). Experiments also show that a parametric gain improvement of 10 dB is achieved in FOPA with double-pass pump configuration at 1.05 W pump power, and gain slope of 47.5 dB/W has been achieved. The power penalty at bit error rate 10-6 is found to be within 5 dB for this double-pass FOPA design, which successfully addresses the practicability issue of this special kind of FOPA design. The IRF is extended in fiber optical parametric oscillator (FOPO) to realize double-pass design FOPO. Besides the significant laser tuning wavelength improvement (72 nm @ 0.45 W, limited by wavelength range of tunable bandpass filter), the double-pass pump FOPO achieves as high as 51% threshold power improvement as compared to the conventional configuration, in addition maintaining laser peak stability within 2 dB.